“Real-World” Evaluation of Lipid Oxidation Products and Trace Metals in French Fries From Two Chain Fast-Food Restaurants - Le Gresley, Adam; Ampem, Gilbert; De Mars, Simon; Grootveld, Martin; Naughton, Declan P. (Frontiers in Nutrition, 2021)
Differences in lipid oxidation products (LOPs) and trace metal concentrations of French fry samples found between two global chain fast-food restaurants in the UK were investigated using high-resolution proton nuclear magnetic resonance (1H NMR) and inductively coupled plasma-optical emission spectrometry (ICP-OES) analyses, respectively, of extracts derived therefrom. Over the course of 3 days and 3 different diurnal time periods, samples of French fries (FFs) were analyzed, and comparisons of two different oil extraction methods were undertaken for the two restaurants involved. The magnitude of concentrations of LOPs extracted from FFs is discussed. Significant differences between 6/7 aldehyde classifications, and aluminum, manganese, vanadium, lead, iron, copper and nickel levels between samples from the two restaurants are also reported. Redox-active transition and further trace metal concentrations inversely correlated with FF oil sample LOP contents; this suggested an antioxidant rather than a pro-oxidant role for them.